Identification and interpretive ranking of factors affecting the improvement of agility in business process management - Sadegh Hasani Moghadam; Mohammad Mahdi Mohtadi; Hossein Bazargani; Ali Taheri; Mohsen Miri (تصمیم گیری و تحقیق در عملیات)
Purpose: The main goal of this study is to present a novel model for managing organizational processes possessing the necessary agility in complex situations. One of the most critical requirements of such a model is using systems thinking and a soft operations research approach because the methods introduced in the background to achieve the agility of the process management generally include fragmentary optimization because of the one-dimensional view and the lack of a system view to identifying agility variables in process management.Methodology: In this study, an attempt was made to provide a comprehensive model using the interpretative paradigm's capabilities. To this end, the main components were identified using the meta-synthesis technique and interviews with eighteen experts. Further, components were prioritized by using the interpretative ranking process.Findings: The findings show that the process leadership component is given first priority based on the interpretive ranking. Therefore, organizations that want to be agile in their process management system should consider leadership characteristics in processes to implement transformational systems. After that, the results showed that environmental awareness, knowledgeable and competent human resources, organizational learning dimension, contingent and appropriate structures, governance, improvisation-based strategy-making, technological infrastructure, dynamic adaptation, culture, and creative sustainability are prioritized, respectively.Originality/Value: Using soft operations research techniques, including the interpretive ranking process, in designing an agile model for managing business processes will significantly help process organizations in complex and dynamic environments to simultaneously exploit the benefits of stability in managing processes and dynamism coming from being agile.